The French Way : How France Embraced and Rejected American Values and Power - Kuisel, Richard F. (Book collections on Project MUSE., 2012)
There are over 1,000 McDonald's on French soil. Two Disney theme parks have opened near Paris in the last two decades. And American-inspired vocabulary such as "le weekend" has been absorbed into the French language. But as former French president Jacques Chirac put it: "The U.S. finds France unbearably pretentious. And we find the U.S. unbearably hegemonic." Are the French fascinated or threatened by America? They Americanize yet are notorious for expressions of anti-Americanism. From McDonald's and Coca-Cola to free markets and foreign policy, this book looks closely at the conflicts and con